Influence of maternal socioeconomic deprivation and living environment on newborn bloodspot 25-hydroxyvitamin D levels - Högler, Wolfgang; Tischlinger, Katharina; Fraser, William D.; Tang, Jonathan C. Y.; Uday, Suma (Frontiers in Endocrinology, 2022)
Objectives: Vitamin D deficiency in neonates can have life-threatening consequences, hence the knowledge of risk factors is essential. This study aimed to explore the effect of maternal socioeconomic status (SES) on newborn 25-hydroxyvitamin D (25OHD) concentrations. Design: Over two 1-week periods (winter and summer 2019), 3000 newborn heel prick dried blood spots (DBS) and additional data, at a newborn screening laboratory (52° N, West Midlands, UK) were gathered. Post code was replaced with lower layer super output area (LSOA). Index of Multiple Deprivation (IMD) quintiles for the corresponding LSOA was used to assess SES [quintile one (Q1): most deprived 20%, quintile five (Q5): least deprived 20%]. Each of the seven domains of deprivation were examined (income, employment, education, health, barriers to housing and services, crime and living environment). 25OHD was measured on 6mm sub-punch from DBS using quantitative liquid chromatography tandem mass spectrometry and equivalent plasma values were derived. Results: In total 2999 (1500 summer-born, 1499 winter-born) newborn DBS (1580 males) were analysed. Summer-born newborns had significantly higher 25OHD (IQR) concentrations [49.2 (34.3; 64.8) nmol/l] than winter-born [29.1 (19.8; 40.6) nmol/l, p<0.001]. 25OHD levels varied significantly between the different IMD quintiles in the whole (p<0.001) and summer-born cohort (p<0.001), but not in the winter-born cohort (p=0.26), whereby Q1 had the lowest 25OHD concentrations. Among the domains of deprivation, living environment had a significant influence on 25OHD levels (β=0.07, p=0.002). In this subdomain, 25OHD levels varied significantly between quintiles in the whole (p<0.001) and summer-born cohort (mean 25OHD Q1 46.45 nmol/l, Q5 54.54 nmol/l; p<0.001) but not in the winter-born cohort (mean 25OHD Q1 31.57 nmol/l, Q5 31.72 nmol/l; p=0.16). In a regression model, living environment was still significant (p=0.018), albeit less than season of birth and ethnicity. Conclusion: Among the seven domains of deprivation, maternal living environment had the greatest effect on newborn 25OHD levels. Whilst improved living environment positively influenced vitamin D status in summer-born babies, winter-born had low 25OHD levels irrespective of environment. Strategies such as enhanced supplementation and food fortification with vitamin D should be considered to overcome the non-modifiable main risk factors for vitamin D deficiency.